Arbuscular mycorrhizal fungi for Jatropha production - Supattra Charoenpakdee (2018)
© Springer Science+Business Media New York 2012. Arbuscular mycorrhizal fungi(AMF) are keystone mutualists inhabiting roots of most plants including the majority of oil crops under cultivation. Therefore, sustainable yield of Jatropha (Jatropha curcasL.) in cultivation is likely to benefit from the inclusion of AMF in crop management cycles. Studies undertaken on acid and alkaline soils in a range of site conditions (productive cropping land, degraded land, mine spoil) indicate close association between Jatropha and AMF since roots were often heavily colonized by AMF in the field. Although a diverse range of AMF genera and species have been identified in the rhizosphere of Jatropha, not all are likely to be effective for sustainable production of Jatropha in plantations. For example, of 34 species of AMF in the rhizosphere of Jatropha in Thailand, only a few species were able to be trapped by Jatropha seedlings. Techniques for assessing the need for inoculation and approaches for inoculum production are discussed. The role of AMF in alleviating stresses is discussed in relation to (1) nutrient and water constraints that are likely to be the main factors limiting the production of Jatropha in many regions of the world and (2) the presence of heavy metals and salinity that will also be challenging for this crop.